Analisis Kepedulian Masyarakat dalam Menjaga Pelestarian Lingkungan Daerah Aliran Sungai Desa Pendolo Kec. Pamona Selatan Kab. Poso Sulawesi Tengah - Fitriyaningsi; Julien Biringan; Telly Delly Wua (Tumoutou Social Science Journal, 2026)
This study aims to evaluate community awareness and environmental conservation efforts in the Pendolo Village Watershed (DAS), focusing on community attitudes, participation, and behavior in maintaining river sustainability, as well as the government's role in supporting and collaborating with the community. This study used a descriptive qualitative approach, collecting data through in-depth interviews, field observations, and documentation studies, to obtain a comprehensive picture of watershed environmental conservation practices. The results indicate that the majority of Pendolo Village residents have a positive attitude toward the importance of river sustainability. Community participation is reflected in mutual cooperation activities, river cleanups, and environmental maintenance, although the level of individual involvement varies. The government's role is evident through facilitation, guidance, and the provision of program support that encourages collaboration with the community. In conclusion, watershed sustainability in Pendolo Village depends heavily on the synegy between the community and the government. Sustainable efforts involving increasing environmental awareness, strengthening community participation and consistent support from government policies and programs are key to maintaining river environmental sustainability.